SEXUALITY AND EMOTIONAL HEALTH - do Amparo Rocha Caridade, Maria (2010)
Psychoanalysis links the psychic and emotional suffering, to the question of dissatisfaction, particularly sexual dissatisfaction. This takes us to the understanding that the pleasure has a special place in the construction of human well-being, and in our emotional health. This well-being comes not only from conquered pleasures, but how we welcome the life in its entirety, in their dimensions pleasurable and suffered, in his agony and its ecstasies. In this text I analyze the "individual alone", the “individual separate" as the most natural condition of our reality. From it we are challenged to the exercise of the encounter with someone and this will mitigate our agony of feeling poor and incomplete. . Thus love is highlighted as restless search, as something that we lack, and keep us away from the fullness. Finally will focus on sexuality as one of the components of people's emotional health.